Photochemical Reaction of ihydroartemisinin esters - Sung et al, Tran Van (Vietnam Journal of Chemistry, 2014)
Photochemical reaction of three dihydroartemisinin esters: acetate, benzoate and succinate under 254 nm UV light in CH2Cl2 have been studied. The result showed, that these artemisinin derivatives are easily decomposed forming different elimination and rearrangement compounds.